Reactive transport modelling of a cement backfill for radioactive waste disposal. (September 2018) - Wilson, James C.; Benbow, Steven; Metcalfe, Richard
Abstract: Cementitious materials are included in many geological disposal facilities for radioactive wastes, including the UK candidate backfill material Nirex Reference Vault Backfill (NRVB). As part of an ongoing programme of work to assess NRVB performance, 1-D reactive-transport models have been constructed to simulate reaction with different illustrative groundwater compositions. Variant cases were also produced to explore the effect of model assumptions on the predicted behaviour of the backfill. Depending on groundwater composition, cement alteration pathways included: carbonation; external sulphate attack; chloride attack; the formation of magnesium-rich solids; and the precipitation of secondary aluminosilicate minerals. In general, the models suggest that the pore space in backfill associated with radioactive waste disposal systems is likely to become clogged (to some degree) over time close to backfill-rock interfaces resulting in a reduction in capacity for solute transport. However, the models do not include all relevant process couplings which is potentially, an area for further work.